RESEARCH ON THE PENTAHELIX USING VOSVIEWER AND BIBLIOSHINY - Hasna, Dhia Alifia Izdihar; Yuadi, Imam (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
This study aims to track the advancement of "Pentahelix"-related research. Scopus searches were used for this research. A flowchart illustrating the stages of the bibliometric analysis employed in this study's research methodology is provided. Software like Biblioshiny and VOSviewer are utilized as research aids. Forty-seven documents were included in the search results, exported as RIS and BibTex files, and processed using the VOSviewer and Biblioshiny software. It is known from the search results that there are 5 clusters and six authors who work together to write scholarly publications on "Pentahelix." "Pentahelix" research varied from year to year. Padjajaran University is the affiliate with the most publications. Indonesia has the most publications, followed by Australia, China, Ethiopia, Kenya, Korea, Malaysia, Mexico, Spain, England, and Italy. IOP Conference Series: Earth and Environmental SCI is a publication source with many scientific papers on the "Pentahelix," it is the affiliate with the most publications. Indonesia has produced the most "Petahelix" papers overall. The findings of this study will help government sector activists work together to advance the timely study of their respective scientific domains.Keywords: Pentahelix, VosViewer, Biblioshiny, Scopus.